Braska [large type] - Dundee, Wayne D. (Dundee, Wayne D. Braska, 2026)
"After six years behind bars for a crime he didn't commit, Virgil "Braska" Smith returns home with one goal: rebuild the life he sacrificed to save his younger brother. But instead of the home he left behind, he finds only abandonment and betrayal. His brother has disappeared-leaving behind his wife, his child, and the family ranch Braska went to prison to protect. Fueled by anger and a need for answers, Braska sets out across the rugged frontier to track him down. Along the way, he battles lawless men, faces dangerous terrain, and proves his grit and decency despite the "ex-con" label that shadows him. The trail leads him to a remote corner of New Mexico, where Braska will confront not only his brother's choices but also the kind of man he wants to be. With danger at every turn and his past weighing heavy, Braska's journey is one of justice, courage, and survival in a land as unforgiving as the men who roam it."--